Penerapan Metode MOOSRA Dalam Seleksi Pemberian Bantuan Sosial Tahunan Perusahaan - Siti Nurhalizah; Yanto Murnihati Waruwu; Agung Triayudi; Mesran (STMIK Budi Darma, 2023)
Provision of social assistance in the form of cash organized by the company,in order to support economic growth everyone is entitled to receive social assistance.The social assistence provided certaily takes into account many things that must br the basis for making the right decisoin so that the funds or assistance are right on targert.To support the organizing committee for provinding social assistance,of course,asses sereval main factors which will from the basis for evaluating each member,and these assesment factors consist of general,ecenomic,skill and discipline assesments. To support eeffectitiveness in determining the recipients of social assistance from the company,the right decision is made to determine the appropriate criteria for receiving social assistence and of course this is the most important policy in the company so that the funds are right on target.This software is built based on a decision support system that has the ability to facilitate a management process in making the right decision in receiving a company’s annual social assistence,using the Multi-Objective Optimization On the Basis of Simple Ration Analysis Method.